Implementation of the Independent Curriculum Policy in Guidance and Counseling Subjects - Disa Sri Ilma Adhitya; Anton Anton; Riska Meisyi Putri; Anggia Pratiwi (Communautaire: Journal of Community Service, 2025)
The Merdeka Curriculum emphasizes student-centered learning, instructional flexibility, and the development of character and competencies. The curriculum provides opportunities for Guidance and Counseling (GC) services to become more adaptive, holistic, and responsive to students’ developmental needs. This study examines the implementation of GC services at Junior high school within the Merdeka Curriculum framework. The findings show that GC services have become an integral part of supporting students’ personal, social, academic, and career development. Implementation involves adjustments in service strategies, collaboration among GC counselors, subject teachers, and homeroom teachers, as well as the use of technology for needs assessment, individual planning, and responsive services. The curriculum has been implemented gradually, supported by school management readiness and teachers’ willingness to adapt. Its impact is reflected in increased student participation, more contextual learning experiences, and the shifting role of teachers toward facilitators. However, challenges remain, including uneven teacher understanding of instructional materials, limited collaboration within learning communities, and suboptimal use of innovative learning media for differentiated instruction. Therefore, this study recommends strengthening systematic training, providing continuous mentoring, and optimizing the use of the Merdeka Mengajar digital platform.